Pd-catalyzed enantioselective intramolecular Heck reaction to access disubstituted dihydroisoquinolinone with a terminal olefin - Sanliang Li (KeAi Communications Co. Ltd., 2021)
A first palladium-catalyzed asymmetric intramolecular Heck reaction for the construction 3,4-dihydro-1-(2H)-isoquinolinone containing the quaternary carbon chiral center has been developed. The salient features of this reaction include high efficiency, high enantioselectivity, the novel chiral ligand and diverse transformations.